2011
DOI: 10.1105/tpc.110.074278
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Control of Arabidopsis 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase by Protein Phosphatase 2A

Abstract: Plants synthesize a myriad of isoprenoid products that are required both for essential constitutive processes and for adaptive responses to the environment. The enzyme 3-hydroxy-3-methylglutaryl-CoA reductase (HMGR) catalyzes a key regulatory step of the mevalonate pathway for isoprenoid biosynthesis and is modulated by many endogenous and external stimuli. In spite of that, no protein factor interacting with and regulating plant HMGR in vivo has been described so far. Here, we report the identification of two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 65 publications
0
95
0
Order By: Relevance
“…Two or more B56 isoforms regulate dephosphorylation of the BAK1 coreceptor (Segonzac et al, 2014), the brassinosteroid-signaling transcription factor BZR1 (Tang et al, 2011), and the brassinosteroid receptor BRI1 (Wang et al, 2016). Both Arabidopsis B55 isoforms interact with nitrate reductase (Heidari et al, 2011), and at least two B72 (clade II) isoforms interact with 3-hydroxy-3-methylglutaryl-CoA reductase (Leivar et al, 2011). These data suggest that, in plants at least, many PP2A subunit isoforms share some functional overlap.…”
Section: Retention Of Duplicated Pp2a Subunit Genesmentioning
confidence: 77%
See 2 more Smart Citations
“…Two or more B56 isoforms regulate dephosphorylation of the BAK1 coreceptor (Segonzac et al, 2014), the brassinosteroid-signaling transcription factor BZR1 (Tang et al, 2011), and the brassinosteroid receptor BRI1 (Wang et al, 2016). Both Arabidopsis B55 isoforms interact with nitrate reductase (Heidari et al, 2011), and at least two B72 (clade II) isoforms interact with 3-hydroxy-3-methylglutaryl-CoA reductase (Leivar et al, 2011). These data suggest that, in plants at least, many PP2A subunit isoforms share some functional overlap.…”
Section: Retention Of Duplicated Pp2a Subunit Genesmentioning
confidence: 77%
“…Arabidopsis B subunits have been named according to the convention for mammalian isoforms: B, B9, or B99 followed by a Greek letter (Terol et al, 2002;Farkas et al, 2007;Leivar et al, 2011). As noted recently for the B56 family (Sommer et al, 2015), this convention is easily misconstrued to imply orthology with mammalian isoforms.…”
Section: Arabidopsis B Subunit Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that OSER structures also accumulate endogenous HMGR protein, with concomitantly reduced HMGR transcript levels. Thus, the membrane availability induced by 1S:GFP somehow stabilizes the chimera and also, the endogenous HMGR, which was previously found in several plants to be submitted to ongoing degrading processes (Korth et al, 2000;Leivar et al, 2011;Pollier et al, 2013). Other endogenous and heterologous ER membrane proteins are also stabilized in OSER structures (Kochevar and Anderson, 1987;McLaughlin et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…This is fully consistent with the hypothesis that variations of HMGR activity in response to changes in the flux of the MVAderived isoprenoid pathway occur mainly via posttranslational control , although the precise nature of this regulatory mechanism remains to be established. HMGR activity levels in FPSsilenced plants may be up-regulated through changes in the phosphorylation status of the enzyme (Dale et al, 1995;Douglas et al, 1997;Leivar et al, 2011) and/or protein degradation mechanisms involving the ERAD protein quality control system (Doblas et al, 2013;Pollier et al, 2013). In any case, an enhancement of HMGR activity concomitant to a reduction of FPS activity could lead to the accumulation of MVA pathway intermediates upstream of FPP that might cause the observed phenotype.…”
Section: Down-regulation Of Fps Activity In Arabidopsis Amirna-based mentioning
confidence: 99%